The “Dark Side” of Community Social Work: An Instrument of Control or a Promoter of Citizen Participation? Reflections on the Results of a Research Project - Cecchi, Sergio (Italian Sociological Review, 2022)
This article discusses the ideas expressed by a group of social workers of the local authorities in a region of north-eastern Italy (Friuli Venezia Giulia) about community social work. Since renewed scientific and operational interest on the part of the social work in community intervention has coincided with the emergence of neoliberal policies to contain spending on welfare systems, this article seeks to understand whether social workers view community social work as a tool to compensate for cuts in social spending or, rather, as a strategy to promote an independent social and political awareness on the part of citizens.